Effects of field-conditioned alfalfa hay on the winter performance of weaned heifer calves - Smith, E.F.; Richardson, D.; Fairbanks, G.E.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This feeding trial was to determine the effects of various field-conditioned alfalfa hays on the winter performance of heifer calves. Second-cutting alfalfa was field-conditioned or processed as follows: 1. Control-mowed, raked, baled. 2. Crushed-mowed, crushed with one smooth steel roll and a spiral-grooved rubber roll, raked and baled.
Keywords: Beef; Alfalfa hay; Performance